Efficiency improvement of GaN-on-silicon thin-film light-emitting diodes with optimized via-like n-electrodes. (27th June 2017) - Feng, Bo; Deng, Biao; Fu, Yi; Liu, Le Gong; Li, Zeng Cheng; Feng, Mei Xin; Zhao, Han Min; Sun, Qian
Abstract: This work reports a significant improvement in efficiency by optimizing the via-like n-electrode architecture design of a GaN-based thin-film LED grown on a 6-inch silicon substrate. The external quantum efficiency of the as-fabricated 1.1 mm × 1.1 mm via-thin-film LED chip at 350 mA was increased by 11.3% compared to that of a vertical thin-film LED chip with a conventional finger-like n-electrode. Detailed analysis of encapsulation gain and false color emission patterns illustrated that the significantly improved LED performance was due to enhanced light extraction efficiency and more uniform current spreading, both of which can be attributed to the optimized via-thin-film chip structure. Minimizing the light loss at the periphery of the Ag mirror was demonstrated to be a critical factor for improving light extraction, rather than simply replacing the finger-like n-electrodes with via-like ones. After encapsulation, the median blue lamp power and the wall-plug efficiency of the via-thin-film LED at 350 mA reached 659 mW and 63.7%, respectively.